BERSIWAK DALAM Q.S. SABÂ:16 DAN HADIS BUKHARI NO 887 PERSPEKTIF TAFSIR ILMI - Junnifar, Ali; Tresnasari, Ery (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2021)
Siwak which has many advantages is one of the themes that can be raised to support the existence of scientific interpretation. The more advanced the development of science and technology, the scientific interpretation will be more in line with science and the times. This research is entitled “Bersiwak in Q.S. Sabâ (34):16 and Hadith Bukhari no. 887 “Scientific Tafsir Perspective”, raised from the difference between groups that reject scientific interpretation and groups who accept scientific interpretation, where this thesis supports scientific interpretation by raising the siwak mentioned in the verses of the Qur'an and many mentioned in the hadith maqbul Siwak comes from wood Arok (Salvadora persica) has many advantages that have been widely studied scientifically and have been published in scientific journals. But in reality, miswak is less superior when compared to ordinary toothbrushes and toothpaste. By using qualitative methods and a library research approach, the study of understanding